Analysis of User Acceptance of Electronic Medical Record Systems Using the Technology Acceptance Model (TAM) - Amelia, Meilany; Susanty, Sri; Prasetya, Fikki (Jurnal Ilmiah Kesehatan (JIKA), 2025)
User acceptance is a key determinant of the successful implementation of Electronic Medical Records (EMR) in hospitals. This study aimed to analyze the factors influencing EMR acceptance at Bhayangkara Level III Hospital Kendari using the Technology Acceptance Model (TAM) approach. A cross-sectional study was conducted involving 114 healthcare workers selected through simple random sampling. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with SmartPLS version 4.0. Perceived ease of use had a significant effect on perceived usefulness (β = 0,760, p < 0.001) and user attitude (β = 0,464, p < 0,001). Perceived usefulness affected user attitude (β = 0,368, p < 0,001) and actual use (β = 0,534, p < 0.001), but had no direct effect on behavioral intention (p = 0,167). User attitude strongly influenced behavioral intention (β = 0,793, p < 0,001), which in turn affected actual use (β = 0,384, p < 0,001). Perceived usefulness acted as a partial mediator between ease of use and attitude, while attitude served as a full mediator between perceived usefulness and behavioral intention. Behavioral intention did not mediate the relationship between perceived usefulness and actual use. A user-friendly system design and demonstrable benefits are essential to foster positive user attitudes and encourage EMR adoption.